Diabetes mellitus and multiple myeloma; common features of two distinct entities. Issue 5 (25th May 2022) - Tentolouris, Anastasios; Ntanasis‐Stathopoulos, Ioannis; Eleftheriadou, Ioanna; Malandrakis, Panagiotis; Tzeravini, Evangelia; Gavriatopoulou, Maria
Abstract: Diabetes mellitus (DM) has attained the status of a global pandemic. Cardiovascular disease (CV) was the leading cause of morbidity in people with type 2 DM, however, a transition from CV to cancer as the leading contributor to DM related death has been observed lately. Multiple myeloma (MM) is the second most common haematological malignancy. Obesity is a common risk factor for both DM and MM. Although data are limited, studies have shown that DM might be associated with increased risk for the development of MM. The presence of DM might affect the course of patients with MM, since hyperglycemia may have an impact on both the efficacy and the adverse effects of antimyeloma therapy. In parallel, DM and MM share common clinical presentations, such as nephropathy, neuropathy, and CV. In terms of antidiabetic medications, metformin might present a synergistic effect with antimyeloma drugs and also prevent some of the adverse effects of these drugs; pioglitazone might have favourable effects when given as add on treatment in people with relapsed or refractory MM. No clinically important interactions have been observed between antidiabetic agents and the most commonly used antimyeloma drugs. Further data are needed to examine the effect of all classes of antidiabetic medication on MM and its complications. A baseline assessment of risk factors for glucose intolerance and close monitoring of glucose levels during therapy is strongly suggested for patients with MM.